Basque-English, English-Basque Dictionary - Aulestia, Gorka, 1932- (Book collections on Project MUSE., 1992)
A condensed version of two much larger works, the Basque-English Dictionary and the English-Basque Dictionary (both published by the U. of Nevada Press), containing definitions of the most commonly used Basque and English words, primarily for students involved in the study of either language. Annotation copyright by Book News, Inc., Portland, OR.